Old trees are perceived as a valuable element of the municipal forest landscape - Suchocka, Marzena; Wojnowska-Heciak, Magdalena; Błaszczyk, Magdalena; Gawłowska, Agnieszka; Ciemniewska, Joanna; Jarska, Agata; Heciak, Jakub; Pachnowska, Beata (PeerJ, 2022)
Urban trees are important to maintain biodiversity and, therefore, need public acceptance. Few studies, however, have addressed the topic of social acceptability of old trees. The aim of this research was to examine city residents’ perception of old trees, including hollow-bearing ones, mainly in the aspect of safety and aesthetics. A total of 448 Warsaw municipal forest’ users expressed their opinions by completing an online questionnaire. Several methods were used to analyse the results of the study: the Chi-square test of independence, the Kruskal–Wallis H test, the Mann–Whitney U test and the Quartimax method of factor rotation analysis. The results revealed a correlation between the frequency of forest visits and the level of sensitivity toward old trees, which translates to less radical notion of danger and less radical decisions about cutting such trees down. Age of the respondents (56+) was a factor contributing to higher willingness to protect and care for old trees. The results also indicated that outdoor activity in the urban forest may increase ancient trees acceptance by developing emotional connection with them, and eventually contribute to their protection.
Keywords: Municipal forest; Old hollow trees; Social survey; Forests’ visitors